IMPLEMENTASI PENDEKATAN FUNGSIONAL DALAM PEMBELAJARAN BAHASA ARAB MELALUI METODE COMMUNITY LANGUAGE LEARNING - Riansyah, Ahmad; Wasilah, Wasilah; Rohayati, Enok; Krisandi, Willa (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Arabic language learning with a functional approach through the Community Language Learning (CLL) method aims to develop students' communication skills in real contexts. This approach emphasizes language as a tool for social interaction, not just grammatical rules. In practice, CLL encourages collaboration between students in a supportive atmosphere, thereby increasing self-confidence and practical understanding of the language. Teachers act as facilitators in creating participatory activities such as group discussions and role-playing. Technology integration in CLL also enriches the learning experience and encourages student independence. Real performance-based assessments are used to measure students' communication skills. In addition to linguistic aspects, this approach also fosters character values such as empathy and cooperation. Thus, the functional approach through CLL is expected to produce a generation that is communicative, collaborative, and sensitive to socio-cultural values in facing global challenges.